PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN PA PI (PAPAN PINTAR) TERHADAP MINAT BELAJAR SISWA KELAS I SD PADA PEMBELAJARAN MATEMATIKA: Penelitian Kuantitatif - Nur Hamidah, Laily; Thamrin Hidayat, Muhammad; Nafiah, Nafiah; Hartatik, Sri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to test the effect of using Pa Pi (Smart Board) learning media on the learning interests of first grade elementary school students in mathematics subjects. The background of this research stems from the low interest in learning mathematics among elementary school students, which is caused by monotonous and less interactive teaching methods. Pa Pi media was developed to present addition material in a concrete and enjoyable way by utilizing unused materials such as wooden boards, cans, sticks, and straws. This research used a quantitative method with a pre-experimental design, specifically the one-group pretest-posttest model. The research subjects consisted of 24 first-grade students at UPT SDN 106 Gresik. The sample used was a saturated sample, as the entire population was included. The instrument used was a student learning interest questionnaire. Data were analyzed using the Shapiro-Wilk normality test and paired sample t-test with the help of SPSS version 25. The results showed a significant difference between the pretest and posttest scores. The average pretest score was 25.38, which increased to 29.63 on the posttest, with a significance value of 0.000 < 0.05. This indicates that the use of Pa Pi learning media has a significant effect on increasing students' learning interest. Therefore, Pa Pi media can serve as an innovative and effective alternative learning tool to enhance elementary school students’ interest in learning, particularly in mathematics.